The diagnostic value of third-generation nanopore sequencing in non-tuberculous mycobacterial infections - Zhao, Chun-Yan; Song, Chang; Lin, Yan-Rong; Nong, Ying-Xing; Huang, Ai-Chun; Xi, Shao-Yong; Wei, Xiao-Ying; Zeng, Chun-Mei; Xie, Zhou-Hua; Zhu, Qing-Dong (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThis study aimed to investigate the diagnostic value of nanopore sequencing technology in non-tuberculous mycobacterial pulmonary disease (NTMPD) and compare it with traditional culture methods.MethodsA retrospective analysis was conducted on 225 suspected NTMPD patients admitted to the Fourth People’s Hospital of Nanning City from January 2022 to July 2024. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), kappa coefficient, and area under the receiver operating characteristic curve (AUC) of nanopore sequencing, culture, and combined diagnostic methods were compared to evaluate their diagnostic performance. In addition, patients were divided into different groups to investigate the detection of NTMPD by nanopore sequencing technology under different pathogen concentrations, in cases of concurrent Mycobacterium tuberculosis (MTB) infection, and among the elderly (aged > 60 years).ResultsAmong 139 NTMPD samples, nanopore sequencing detected positives in 113 cases, with a sensitivity of 81.3%, PPV of 99.1%, NPV of 76.6%, kappa coefficient of 0.759, and AUC of 0.901, demonstrating high specificity (98.8%) comparable to culture. The combined diagnostic approach significantly improved the sensitivity (90.6%), NPV (98.4%), kappa coefficient (0.862), and AUC (0.942) of NTMPD diagnosis. Nanopore sequencing showed superior diagnostic value in samples with various bacterial concentrations and in cases of concurrent MTB infection.ConclusionThird-generation nanopore sequencing technology serves as a rapid and effective diagnostic tool, which may profoundly impact the current diagnosis of NTMPD.